Platelet receptors for human Factor VIII/von Willebrand protein: functional correlation of receptor occupancy and ristocetin-induced platelet aggregation. - Kao, K J (1979)
Previous studies of von Willebrand disease indicate that a deficiency of blood clotting Factor VIII/von Willebrand factor (FVIII/vWF) activity is responsible for the failure of platelets to participate fully in the initial stages of hemostasis. We have recently identified specific FVIII/vWF binding sites on platelets, suggesting that the interaction of these sites with FVIII/vWF may be functionally important in the development of platelet clumps. We have now studied how different ristocetin concentrations, various known platelet aggregation inhibitors, and the exposure of platelets to proteases affect the ability of platelets to bind FVIII/vWF and to form aggregates. Our results demonstrate a highly significant linear correlation between the degree of FVIII/vWF receptor binding and the extent of ristocetin-induced platelet aggregation. Because neither FVIII/vWF binding nor platelet aggregation occurs after platelets are exposed to low concentrations of proteases, the FVIII/vWF receptors must be in the platelet membrane. We conclude that the interaction between FVIII/vWF protein and its receptors on the platelet membrane is an important mechanism by which platelet aggregation occurs during primary phase hemostasis.